MEMAHAMI RELASI KONSEP FUNGSI, BENTUK DAN MAKNA ARSITEKTUR RUMAH TINGGAL MASYARAKAT KOTA PESISIR UTARA DI KAWASAN JAWA TIMUR (Kasus Studi Rumah Tinggal di Kampung Karangturi dan Kampung Sumber Girang, Lasem) - Fauzy, Bachtiar; ., Antariksa; Salura, Purnama (DIMENSI (Journal of Architecture and Built Environment), 2012)
Housing architecture in the Kampong Chinatown Karangturi - Lasem located in the North Coast of Java was the architecture of the Chinese community that had the character of the Chinese architectural style, this phenomenon is reinforced by the data entry of Chinese culture that took place since the 13th century. This study revealed how to understand the concept relation of function, form and meaning of urban housing architecture in the North Coast region of East Java. Case study looked at the extent of housing architecture in the Kampong Sumber Girang, Lasem as clients affected by the housing architecture in Kampung Karangturi as a patron. This study took the method of structuralism and typomorphology approach to unravel the phenomenon of urban coastal architecture concept of relation. The results of this study showed that to understand the concept relations of function, form and meaning of coastal architecture could be determined through the study of Javanese human behavior concept of relation, which at the end revealed the surface structure and deep structures of coastal architecture.